Implementation of Active Reading Movement as a Strategy to Improve Literacy in SDN 1 Kunjang-Kediri: Implementasi Gerakan Aktif Membaca sebagai Strategi Peningkatan Literasi di SDN 1 Kunjang-Kediri - Akbar , Ali; Akmaliya , Siti Nisaaul; Rahmalia , Hilda Amanda; Qomariah , Luluk Asti; Kholil , Aumanda Nur Faiza (International Consortium of Education and Culture Research Studies, 2025)
General Background: The development of reading literacy is a fundamental aspect of improving the quality of basic education and fostering critical thinking skills among students. Specific Background: In response to low reading fluency and vocabulary comprehension among fifth and sixth-grade students, KKN-P Group 04 from Universitas Muhammadiyah Sidoarjo implemented an active reading movement at SDN 1 Kunjang, Ngancar District, Kediri Regency. Knowledge Gap: Despite nationwide literacy initiatives, structured and continuous programs that specifically address the dual challenges of reading fluency and vocabulary mastery in rural elementary schools remain limited. Aims: This study aims to enhance students’ reading skills and vocabulary understanding through a focused, participatory literacy intervention. Results: The program was conducted over four weeks, with daily sessions from Monday to Thursday and weekly evaluations on Fridays. Strategies included group reading activities, vocabulary discussions, and regular assessments. The intervention yielded significant improvements in both reading fluency and vocabulary comprehension, as evidenced by student progress charts and comprehensive activity documentation. Novelty: The program’s structured approach, combining daily engagement with continuous evaluation, offers a replicable model for literacy enhancement in elementary education. Implications: This initiative demonstrates that systematic literacy programs can effectively address foundational educational challenges and may serve as a practical reference for other schools aiming to improve student literacy outcomes through sustained and adaptive methods. Keywords: Literacy, Reading Fluency, Vocabulary, KKN-P UMSIDA, Elementary Education Highlights: Daily structured reading activities boost student literacy. Vocabulary discussions improve word comprehension significantly. Replicable program model supports rural school literacy initiatives.